Terminological principles and morphosyntactic terminological variations - Trebar, Blaž (Jezikoslovni zapiski, 2015)
The article deals with terminological principles and terminological variability, with an emphasis on morphosyntactic terminological variations. Examples of such variations were empirically observed in a specialized corpus of texts on computer and information sciences. Based on the examples retrieved, the article presents a typology for describing morphosyntactic terminological variations in Slovenian. It also highlights the logical and conceptual relations established through such terminological variations.